The local stress in the neighborhood of a circular crack under thermal and mechanical loading - E. M. Kartashov; T. V. Anisimova (Тонкие химические технологии)
The long circular cylindrical sample (polymer fiber) with internal insulated circular crack under the action of constant pressure and thermal heating with the heat flow directed along the axis of the cylinder and normally to the plane of the crack is considered. A number of generalizing ratios for the stress intensity factors under thermal and mechanical loading is derived.